2017
DOI: 10.1111/dom.12958
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with LY2409021, a glucagon receptor antagonist, increases liver fat in patients with type 2 diabetes

Abstract: In this cohort of patients with T2D, chronic glucagon receptor antagonism with LY2409021 was associated with glucose-lowering but also demonstrated increases in hepatic fat, hepatic aminotransferases, and other adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 18 publications
7
119
0
Order By: Relevance
“…For instance, it will be interesting to see whether changes in hepatic insulin and glucagon sensitivity (HOMA-IR and the glucagon-alanine index) move in parallel or follow distinct trajectories over time. Moreover, recent research has suggested that disruption of the glucagon-liver cycle (with glucagon receptor antagonists) may also lead to disturbances in lipid metabolism [49]. This has not been addressed in the present study, but needs to be investigated.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, it will be interesting to see whether changes in hepatic insulin and glucagon sensitivity (HOMA-IR and the glucagon-alanine index) move in parallel or follow distinct trajectories over time. Moreover, recent research has suggested that disruption of the glucagon-liver cycle (with glucagon receptor antagonists) may also lead to disturbances in lipid metabolism [49]. This has not been addressed in the present study, but needs to be investigated.…”
Section: Discussionmentioning
confidence: 82%
“…MRIs performed at baseline, 1, 3, 6, and 12 months from first treatment dose; at early discontinuation (if applicable); and at 4 months posttreatment were used to characterize the extent, time course, and reversibility of changes in HFF. More details about the MRI procedure are described in the original study manuscript . For this analysis, HFF was available at baseline, 1 month, 3 months, and at the time of the primary endpoint at 6 months.…”
Section: Methodsmentioning
confidence: 55%
“…As reported, LY2409021 treatment showed significant HbA1c reductions versus placebo (LSM difference, –0.77%; P < 0.001) but not versus sitagliptin (−0.20%; P = 0.383) at 6 months . A significant increase in HFF was seen with LY2409021 versus sitagliptin (LSM difference, 3.72%; P < 0.001) and placebo (4.44%; P < 0.001), accompanied by significant ALT elevations with LY2409021 versus sitagliptin (6.8 U/L; P = 0.039) and placebo (10.7 U/L; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations